Subnival Processes and Subnival Sedimentation Mechanisms, the Pamir-Alay Mts., Tajikistan - Paweł Kroh; Piotr Dolnicki; Adam Łajczak (Land, 2021)
Geomorphological research in the Fann Mountains of the Pamir-Alay has indicated that subnival processes are occurring. Contemporary subnival sediments indicate that complex relationships occur between the snow patches, subnival waters, and ground. Underneath a semi-permanent snow patch, snow melts slowly from the direction of the ground, resulting in a hollow that is filled with sediments produced by wash-down from the river terraces. The energy of subnival waters washes away and displaces sediments present underneath the snow patch, but also causes them to be redeposited. The sediment features imply a significant impact of the relief under the snow patch on the thickness of nival deposits and the nivation mechanism. The sediments also indicate that subnival waters may be under hydrostatic pressure, which has a considerable impact on both the snowmelt and sedimentation processes.